Memory, denial and social traumatism from a Psychoanalysis of Binding Configurations perspective - Maia, Bruna Bortolozzi; dos Santos, Manoel Antônio; Okamoto, Mary Yoko [UNESP] (FapUNIFESP (SciELO), 2023)
Denialist discourses and the downplayed harmful effects of the civil-military dictatorship by high-ranking Brazilian government officials are emblematic examples of negationist attitudes towards narratives of social suffering. This theoretical study addresses the psychological processes of erasing traumatic social memories and their effects on psychic transmission based on psychoanalysis of linking configurations according to Puget and Berenstein. By mobilizing the concepts of social memory, denial, trauma and social trauma, we argue that negating traumatic facts generates a double violence: on the one hand, it produces gaps in history and a non-work linking that favors transgenerational psychic transmissions; on the other, it attacks the individuals’ social belonging and narcissistic constitution. We thus conclude by pointing out the need to create a listening device for social trauma that opposes denial, ensuring the right guaranteed by the Universal Declaration of Human Rights of people’s access to their own history.
Memoria, desmentida y trauma social desde la perspectiva del Psicoanálisis de las Configuraciones Vinculares
Mémoire, négationnisme et traumatisme social dans la perspective de la Psychanalyse des Configurations de Liaison
Keywords: denial; desmentida; liens; linking; memoria; memory; memória; mémoire; négationnisme; psicanálise; psicoanálisis; psychanalyse; psychoanalysis; social traumatism; trauma social; traumatisme social; traumatismo social; vínculos